Die therapeutischen Effekte endothelialer Progenitorzellen beim LPS-induzierten ARDS = Therapeutic effects of endothelial progenitor cells in LPS-induced ARDS - Rafat, Neysan; Dacho, Christine; Krebs, Jörg; Tsagogiorgas, Charalambos; Yard, Benito A.; Beck, Grietje (Anästhesiologie & Intensivmedizin, 2012)
Background: Endotoxin-induced ARDS is characterized by diffuse dysfunction of the microvasculature including increased permeability with edema formation and apoptosis or necrosis of endothelial and epithelial cells. Concomitantly, an increased concentration of circulating endothelial progenitor cells (EPC) was found in septic patients, of which more than half have pulmonary involvement. The number of circulating EPC correlated inversely to disease severity and mortality. Since these EPC were found homing to damaged lung tissue, a reparative process seems to be initiated right after the initiation of vessel damage or degeneration. In the present study we investigated the potential of EPC as a treatment strategy in ARDS.
Gesehen am 23.11.2018